2011
DOI: 10.1111/j.1745-4514.2010.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Quality Assessment of Semi-Dried Squid (Todarodes Pacificus) Treated With High Hydrostatic Pressure

Abstract: The effect of high pressure processing (HPP) on the reduction of microbial growth, dimethylamine (DMA), trimethylamine (TMA) and biogenic amines (BAs) was investigated in semi-dried squid for 28 days at 4C. The semi-dried squid was subjected to 500 MPa for 0 min (HPP-0), 5 min (HPP-5) and 10 min (HPP-10). The number of Morganella morganii and Klebsiella pneumonia in the HPP-10 was less than 1 log cfu/cm 2 throughout the refrigerated storage time. The highest amount (22.16 mg/kg) of DMA was detected in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Squid is a popular seafood in Asian and Mediterranean countries because of its desirable flavor and unique texture (Benjakul and others ; Chen and others ; Gou and others ). Currently, most squids are marketed as frozen or dried product for minimizing the microbial deterioration and nutrition loss (Gou and others ; Benjakul and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Squid is a popular seafood in Asian and Mediterranean countries because of its desirable flavor and unique texture (Benjakul and others ; Chen and others ; Gou and others ). Currently, most squids are marketed as frozen or dried product for minimizing the microbial deterioration and nutrition loss (Gou and others ; Benjakul and others ).…”
Section: Introductionmentioning
confidence: 99%
“…During storage at 4 °C for 10 days, the retention of anthocyanins and ascorbic acid of high-pressure-treated (600 MPa, 15 min) orange juice was found to be 93.4 % and 85.0 %, respectively. Gou et al ( 2012 ) demonstrated that high pressure resulted in increased yield of pectin (20.44 %) as compared to yields obtained by traditional (15.47 %) or microwave (18.13 %) heating. The intrinsic viscosity and average molecular weight of pectin extracted by HPT was much higher than those extracted by traditional heating or microwave compared to commercial pectin.…”
Section: Orangesmentioning
confidence: 94%
“…Therefore, HPT could be a promising alternative to retard the quality deterioration of squid. Gou et al ( 2012 ) demonstrated that HPT (500 MPa, 10 min) of semidried squid effectively retarded the growth of Morganella morganii and Klebsiella pneumonia contributing to the formation of biogenic amines and also inhibited the development of off-fl avors such as dimethylamine and trimethylamine during refrigerated storage. High-pressure processing can reduce or eliminate microorganisms of concern in food without deteriorating product quality or compromising safety, which can justify the substantial capital investment for adopting this technology on an industrial scale.…”
Section: Oystersmentioning
confidence: 99%
“…Hence, squid, particularly dried squid, is usually processed into various products with extended shelf life. Although fully dehydrated fishery products can be stored for much longer periods than semi-dried ones, there is an increasing preference for the latter products owing to their better flavor and tenderness [2,3]. Fully dried and semidried squid have been highly prized in the Far East for their unique flavor and often eaten directly as a snack food, side dishes, or refreshments [4].…”
Section: Introductionmentioning
confidence: 99%
“…Semi-dried squid is usually preserved under frozen and refrigerated conditions; however, the shelf life of refrigerated semi-dried squid is relatively short and predominantly depends on the degree of microbial contamination. Moreover, these methods of preservation may not effectively control microbial contamination [2].…”
Section: Introductionmentioning
confidence: 99%